From Chalk to Click: Digital Skills Teachers Must Have Today - Buaton, Julisesko; Simbolon, Sinta Evenia; Sitanggang, Dede Irma; Winarni, Winarni; Sonia, Gabriella (Asian Journal of Applied Education (AJAE), 2025)
In the era of educational transformation, digital skills are a crucial aspect for teachers in supporting effective learning. Technological developments have changed the educational paradigm towards digitalization, where the teaching-learning process increasingly relies on various digital tools, software, and systems. However, many teachers still face challenges in mastering digital skills that match the needs and demands of modern learning, which has the potential to affect the quality of education in schools. This research aims to analyze the digital skills needed by teachers in the context of educational transformation. The method used is qualitative research with an in-depth interview and observation approach. The research participants consisted of teachers from various disciplines who taught in Junior High Schools (SMP), with the focus of research conducted at Budi Mulia Junior High School, Bogor. This research lasted from February to March 2025. The results of the study show that teachers need skills in the creation of digital learning modules, digital-based assessment systems, and the creation of learning content, such as animated videos. In addition, teachers need not only training related to the use of technology, but also effective pedagogical strategies in integrating technology into learning. Therefore, the training designed must include technical and methodological aspects so that teachers can optimize the use of technology in the learning process.